Left atrial appendage morphology predicts the formation of left atrial appendage thrombus. (5th February 2021) - Negrotto, Sara M.; Lugo, Ricardo M.; Metawee, Mohamed; Kanagasundram, Arvindh N.; Chidsey, Geoffrey; Baker, Michael T.; Michaud, Gregory F.; Piana, Robert N.; Benjamin Shoemaker, Moore; Ellis, Christopher Randall
Abstract: Background: Nonchicken wing left atrial appendage (LAA) morphology is associated with higher risk for stroke in patients with atrial fibrillation (AF) than chicken wing (CW) morphology. Objective: Assess whether LAA morphology predicts the formation of LAA thrombus independent of age, sex, presenting rhythm, left ventricular ejection fraction (LVEF), or anticoagulant use. Methods: A cross‐sectional analysis was performed on patients prospectively enrolled in the Vanderbilt LAA Registry or presenting for transesophageal echocardiogram (TEE) between January 1, 2015, and November 1, 2017 ( n  = 306). Two physicians independently reviewed TEEs interpreted as having LAA thrombus. Determination of LAA morphology, ejection velocity, and presence of thrombus ( n  = 102) were based on 0°, 45°, 90°, and 135° TEE views. The control cohort ( n  = 204) included consecutive AF patients undergoing TEE without LAA thrombus. Results: LAA morphology in patients with LAA thrombus was: 35% windsock, 47% broccoli, and 12% CW. Windsock (odds ratio [OR], 4.0; 95% confidence interval [CI]: 1.7–9.3, p  = .001) and broccoli (OR, 6.6; 95% CI: 2.6–16.6; p  < .001) morphology were higher risk for thrombus compared to CW. Female sex predicted higher‐odds for LAA thrombus (OR, 2.6; 95% CI: 1.4–4.8; p  = .002) as did LAA‐EV < 20 cm/s (OR, 11.12; 95% CI: 5.6–22.1). Anticoagulation use (OR, 0.5; 95% CI: 0.3–0.9; p  = .03) and higher LVEF (OR, 0.95; 95% CI: 0.93–0.98; p  < .001) were associated with lower risk. In patients with a CW morphology who had LAA thrombus, 4 of the 7 had an LAA‐EV < 20 cm/s and acute systolic heart failure with LVEF < 30% or active malignancy. In multivariable linear regression analysis controlling for presenting rhythm, anticoagulant use, age, sex, and LVEF, CW morphology appears relatively protective from LAA thrombus ( p  = .001). Conclusion: CW LAA morphology appears relatively protective against the formation of LAA thrombus.